Conversores híbridos aplicados a audio: estudo comparativo com amplificadores classe D - Frantz, Guilherme Weber (2019)
The convergence of knowledge related to mechanics, electronics and music has resulted in the development of a series of audio devices. Initially, signal amplifiers were developed working in linear region. Due to the efficiency limitations of this form of amplification, the concept of switched amplifiers with a theoretical efficiency of 100% was introduced. However, the high frequencies inherent in its operation add distortion, interference and worsening dynamic response. In order to unite the advantages of both forms of amplification, hybrid amplifiers emerged. The following work aims to propose a hybrid topology of audio signal amplification, called Double Half Bridge + Class AB. To this end, a literature review of the different forms of amplification is carried out, following the design of Class-D amplifier and a Hybrid amplifier, comparing their distortion and efficiency results, aiming to prove the sum of the advantages of the topologies. Both circuits are experimentally tested, resulting in design validation. The hybrid amplifier performed 90% efficiency: more than the theoretical limit of linear amplification (78.5%) and less than the designed Class-D performance (96%). The harmonic distortion of the hybrid circuit remained lower than the switching due to the output power, reaching a minimum value of 0.05%. It is concluded that the amplifier was successful in adding the advantages of both topologies.